Algorithms, Probability, Networks, and Games : Scientific Papers and Essays Dedicated to Paul G. Spirakis on the Occasion of His 60th Birthday - Zaroliagis, Christos; Pantziou, Grammati; Kontogiannis, Spyros; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This Festschrift volume is published in honor of Professor Paul G. Spirakis on the occasion of his 60th birthday. It celebrates his significant contributions to computer science as an eminent, talented, and influential researcher and most visionary thought leader, with a great talent in inspiring and guiding young researchers. The book is a reflection of his main research activities in the fields of algorithms, probability, networks, and games, and contains a biographical sketch as well as essays and research contributions from close collaborators and former PhD students.
Keywords: Computer software; Computer Communication Networks; Computer science; Data structures (Computer scienc; Software engineering; Algorithm Analysis and Problem Complexity; Computer Communication Networks; Computation by Abstract Devices; Data Structures; Information Systems Applications (incl. Internet).; Software Engineering